2019
DOI: 10.1021/acsabm.9b00477
|View full text |Cite
|
Sign up to set email alerts
|

Determinant of ESIPT Mechanism by the Structure Designed for Symmetrical and Unsymmetrical Molecules

Abstract: In this work, we present that different structures lead to different excited state properties based on the investigations of the systems with symmetrical and unsymmetrical properties. Our work shows that the symmetrical and unsymmetrical compounds with a modified structure play key roles in regulating the excited state intramolecular proton transfer (PT) (ESIPT) process. For N,N′-bis(salicylidene)-p-phenyle-nediamine (BSP) and N,N′-disalicylidene-1,6-pyrenediamine (BSD), when they are excited, the torsion ange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The pyridine ring is twisted, and the change of structure leads to the different optical properties. [48] This also proves that the addition of MeOH molecule makes the 2a molecule more prone to proton transfer.…”
Section: Electronic Spectra and Frontier Molecular Orbitalsmentioning
confidence: 74%
“…The pyridine ring is twisted, and the change of structure leads to the different optical properties. [48] This also proves that the addition of MeOH molecule makes the 2a molecule more prone to proton transfer.…”
Section: Electronic Spectra and Frontier Molecular Orbitalsmentioning
confidence: 74%
“…BI is a bifunctional molecule, containing a benzimidazolyl NH group and a hydroxyl OH group. Recently, phototautomerization of different types of molecules by solvent-assisted proton transfer (SAPT) has received extensive attention. In particular, a series of bifunctional molecules experiencing the SAPT reaction attract intense scientific interest for both theoretical investigations and potential applications. Molecules possessing a proton donor (O–H or N–H) or an acceptor (carbonyl oxygen or aromatic nitrogen) may undergo an excited-state proton transfer (ESPT) process upon electronic excitation. Namely, there exist two possible proton transfer (PT) pathways in BI: (1) Type-A, transfer of the H atom of the benzimidazolyl NH to the pyridyl nitrogen; and (2) Type-B, transfer of the H atom of the hydroxyl OH to the pyridyl nitrogen. Numerous studies on the bifunctional BI molecule are reported to investigate the ESPT process experimentally and theoretically. The concerted PT reaction by the Type-B pathway in ethanol is reported .…”
Section: Introductionmentioning
confidence: 99%